Assessment of Accommodation and Space Requirements in Private University Libraries in South East Nigeria in Alignment with Librarians' Registration Council of Nigeria Minimum Standards and Guideline - Ngozi Njideka Okechukwu; Anthonia Ukamaka Echedom; Ngozi Njideka Okechukwu (Universitas Negeri Malang, 2026)
The research was conducted using descriptive survey design to determine the accommodation and space needs in the private universities libraries in South East Nigeria. It was carried out in all the fourteen universities in the area using an observation checklist and structured interviews using Librarians Registration Council of Nigeria (LRCN) criteria. Instruments were checked with the experts and reliability tested, being very consistent. The information was gathered based on on-site visits that allowed observing and communicating with librarians directly. It was analyzed in percentages with a set of 70 as the benchmark of compliance. The methodology was a systematic way of assessing the effectiveness of the libraries in terms of facilities and services against LRCN standards. Findings indicated that the private university libraries in South East Nigeria conformed to LRCN standards of accommodation and space moderately. The number of assessed items, 23, aligns with most libraries (15/23) giving a partial correlation. The most essential facilities like staff offices, reading, ICT rooms, parking and the internet were mostly provided. But there were severe weaknesses in such aspects as accessibility to the special needs individuals, continuous power supply, noise requirements, exhibition facilities, and disaster management policies. Other facilities like common rooms of the staff and reading areas of the children were more or less absent. According to the study, despite the partial adherence to LRCN standards in South East Nigeria by the private university libraries, there is still need to work on the libraries to comply with the standards completely. The management of the university was advised to focus on improving the infrastructural development, inclusion in design, and compliance with the regulatory requirements to improve the effectiveness of the library.